1994
DOI: 10.1111/j.1365-2559.1994.tb00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in expression of basement membrane proteins during tumour progression in oral mucosa

Abstract: 1 9 94) Histopat hology 24, 5 3 1 -5 3 7 Alterations in expression of basement membrane proteins during tumour progression in oral mucosaExpression of three basement membrane proteins-collagen IV, laminin and fibronectin-was studied in normal, hyperplastic, dysplastic and neoplastic conditions of the oral mucosa using immunohistochemistry. Collagen IV and laminin exhibited similar staining patterns, while fibronectin showed a different pattern of expression. The expression of collagen IV and laminin also demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 24 publications
2
30
0
1
Order By: Relevance
“…21,22 In the present study, RCs, and DCs generally exhibited a linear and continuous expression of collagen IV, in agreement with the staining pattern described for normal tissues. On the other hand, KOTs and ameloblastomas presented a highly discontinuous thin linear staining pattern, with Յ50% extension of the BM in 80% and 100% of cases, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…21,22 In the present study, RCs, and DCs generally exhibited a linear and continuous expression of collagen IV, in agreement with the staining pattern described for normal tissues. On the other hand, KOTs and ameloblastomas presented a highly discontinuous thin linear staining pattern, with Յ50% extension of the BM in 80% and 100% of cases, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies confirmed that the structural integrity of the ECM-BM was closely associated with carcinoma formation, development, invasion and prognosis of the patient (40,41). In various carcinomas, the BM usually becomes thin and easily degrades, releasing collagen into the surrounding environment.…”
Section: Discussionmentioning
confidence: 75%
“…During neoplastic invasion, glycoprotein synthesis in the basal membrane is slower and disorganized, leading to permanent loss of continuity. 5 In recognition of this feature, our analysis of oral mucosal squamous cell carcinomas for assessing laminin expression was not done in areas with intense inflammation, to avoid distorting the results.…”
Section: Discussionmentioning
confidence: 99%